2019
DOI: 10.2188/jea.je20170210
|View full text |Cite
|
Sign up to set email alerts
|

Number of Teeth, Oral Self-care, Eating Speed, and Metabolic Syndrome in an Aged Japanese Population

Abstract: These results suggest that maintaining teeth, eating slowly, and using secondary oral hygiene products every day are associated with a lower likelihood of MetS in the aged population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
(41 reference statements)
0
19
0
12
Order By: Relevance
“…This subsequently can lead to intake of soft foods, often laden with fat, sugar, and salt -exactly what people with diabetes should try to avoid [24,79]. For example, the risk for metabolic syndrome was 54% greater in 75-80-year old Japanese with 0-9 teeth remaining, compared to those with 20-28 teeth [80]. Similarly, tooth loss was strongly associated with impaired glucose metabolism in middle-aged Finnish women during 46-years follow up [81].…”
Section: Tooth Lossmentioning
confidence: 99%
“…This subsequently can lead to intake of soft foods, often laden with fat, sugar, and salt -exactly what people with diabetes should try to avoid [24,79]. For example, the risk for metabolic syndrome was 54% greater in 75-80-year old Japanese with 0-9 teeth remaining, compared to those with 20-28 teeth [80]. Similarly, tooth loss was strongly associated with impaired glucose metabolism in middle-aged Finnish women during 46-years follow up [81].…”
Section: Tooth Lossmentioning
confidence: 99%
“…The reason for a male predominance in belching is still unknown. Saito et al reported that men eat food faster than women (14), suggesting that men may swallow air more often during eating. In addition, men generally might prefer carbonated alcohol drinks and they do not hesitate to belch when compared to women.…”
Section: Discussionmentioning
confidence: 99%
“…16 Additionally, some novel confounding factors were also collected, including breakfast frequency and dietary patterns. 17,18…”
Section: Data Collectionmentioning
confidence: 99%